Existence of Nonoscillatory Solutions for a Rational Difference Equation of Higher Order (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we investigate a rational difference equation of higherorder for the existence of nonoscillatory solutions. To prove our main results,we use an inclusion theorem stated and proved in [4]. In this way, we give ananswer of an open problem formulated in [3].